Vietnam series: Four key features of the commercial mediation framework - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2018)
In the first few months of this year I found myself returning to Vietnam a number of times thanks to Vietnamese initiatives in commercial mediation. Most recently I was involved in workshops hosted by the Vietnam Business Lawyer’s Club, the Judicial Academy and the International Finance Corporation (IFC). Given the mediation activity in Vietnam and previous Kluwer posts on aspects of Vietnamese mediation, this post offers an overview of the main features of Vietnam’s legal and institutional framework for commercial mediation.